EMPOWERING FUTURE LEADERS: INTERACTIVE ENGLISH FOR PROFESSIONAL PURPOSES IN MANAGEMENT, ACCOUNTING, AND LAW FOR MALAYSIAN VOCATIONAL STUDENTS - R. A. Widyanti Diah Lestari; Christiani Prasetiasari; Metha Arisandi; Angelina Eleonora Rumengan (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2026)
This community engagement program aims to strengthen students’ English competencies particularly vocabulary enrichment and professional communication, among vocational learners at SMK Gemereh Segamat, Malaysia. The initiative responds to the growing need for English for Professional Purposes (EPP) in management, accounting, and law, driven by Malaysia’s expanding regional economic integration. Activities were designed using interactive and learner centered approaches, combining simulations, contextual dialogues, collaborative tasks, and applied vocabulary practices. The results show significant improvements in students’ confidence, communicative fluency, and understanding of profession-based terminology. The findings underline the importance of practical, engaging English learning strategies that connect language skills with students’ future career pathways.